Intelligent Surveillance Systems: A Review - Mejia Muñoz, Jose Manuel; Mariscal Torres, Adrián; Ortega Máynez, Leticia (Cultura Científica y Tecnológica, 2020)
Security refers to the perceptions about an environment protection, it means without worry of suffer harm. This research offers a literature review about security subject, focused on autonomous surveillance, gathering in a single document the technical novelties about surveillance systems, their applications, and central components. During this research , we observe that deep learning its being applied for surveillance purpose, opening new research horizons, in an area which does not have been significant changes during about ten years, and we also found that new vast datasets are being produced to solve issues regarding security. We have also seen that, in terms of security, deep learning is highly viable to solve problems that have been implicit in security systems for a long time, this being able to turn deep learning into a new breakthrough with respect to systems programmed only by traditional vision algorithms, opening the possibility of becoming a mandatory accessory for security of systems. This research has been limited only on civil area surveillance systems, also we only use scientific articles for this, avoiding commercial technologies.